Career paths of PhD graduates in Eastern and Western Germany - Rehs, Andreas,Fuchs, Michaela (Institute for Employment Research of the Federal Employment Agency, 2020)
This paper investigates the extent to which the returns to gaining a PhD degree depend upon the region of birth, the region where the degree was earned, and the place of work. Eastern Germany serves as an interesting showcase in light of the ongoing debate surrounding the underrepresentation of eastern Germans in top positions in Germany. We examine the career paths of eastern and western German PhD graduates who completed their dissertations between 1995 and 2010. We estimate the returns with regard to obtaining a job suited to their skill level and with high wages. Our data set combines information on PhD graduates and their place of birth collected from data on PhD dissertations in Germany with data from administrative social security records. This record linkage approach provides a unique source of individual employment and wage biographies of eastern and western German PhD graduates. Our findings show that labor market success is affected neither by being born in eastern Germany nor by earning a PhD at an eastern German university. However, the place of work does matter, suggesting that the stark differences between the two parts of Germany with regard to labor market conditions is the main reason for the differences in the labor market prospects of PhD graduates from eastern and western Germany. Dieses Papier geht der Frage nach, ob die regionale Herkunft ein Hindernis für die Inanspruchnahme der Bildungserträge einer Promotion darstellt. Ostdeutschland bietet hierfür aufgrund der anhaltenden Diskussionen über die Unterrepräsentation von Ostdeutschen in bundesdeutschen Spitzenpositionen ein gutes Beispiel. Wir untersuchen die Erwerbsbiografien ost- und westdeutscher Promovierter, die ihre Dissertationen zwischen 1995 und 2010 beendet haben, um herauszufinden, ob ein ostdeutscher Hintergrund die Bildungserträge reduziert. Diese messen wir anhand einer ausbildungsadäquaten Beschäftigung und hoher Löhne. Unser Datensatz kombiniert Informationen zu Promovierten und ihrem Geburtsort mit administrativen Daten und stellt damit einen einmaligen Datensatz für die Untersuchung der Erwerbbiografien ost- und westdeutscher Promovierter dar. Unsere Ergebnisse weisen weder dem Geburtsort noch dem Standort der Universität, an der die Promotion abgelegt wurde, einen signifikanten Einfluss auf die Bildungserträge zu. Eine zentrale Rolle spielt allerdings der Arbeitsort in Ostdeutschland. Er reduziert die Chancen auf hohe Löhne, was die Bedeutung der Unterschiede in den wirtschaftlichen Bedingungen in Ost- und Westdeutschland für die Arbeitsmarktaussichten der Promovierten betont.
10419/222386
Keywords: Graue Literatur; Eastern Germany; overeducation; PhD graduates; record linkage; job-skill mismatch; wages